Sound treated room in a speech and hearing clinic - Murthy SS; Jacob KT (Journal of All India Institute of Speech and Hearing, 1970)
Aucostic environment plays an important role in the field of Audiology and Speech  Pathology  especially  in  conducting  hearing  acuity  tests.    A  suitable aucostic environment is required to carry out free-field tests especially for children and for recording the speech samples of patients with  defective  speech  before, during  and  after therapy.    For  the  above  test  requirements,  the  Speech  and Hearing Clinic should be provided with a satisfactory sound treated room